Development of Teachers' Primary School Skills in Teaching Arabic - Nandang, Ade; Nasrudin, Dindin (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2019)
In Islamic elementary school, Arabic is a compulsory subject that must be taught.In fact, the majority of elementary school teachers are not equipped with enoughcompetence to teach it. This paper aims to describe efforts to improve the competence of elementary school teachers in teaching Arabic. The research method is descriptive qualitative through teacher competency mapping, needs analysis and Focus Group Discussion (FGD). The result of the research shows that Teacher Proficiency Development (TPD) in the form of workshop and teaching practice can be one of alternative in improving the pedagogic and professional competence of elementary school teacher in teaches Arabic. In order for effective TPD program, massive dissemination, advisory and sustainable programming is required involving relevant universities, government, and schools.